THE INFLUENCE OF ACCESSIBILITY ON THE VOLUME OF TUBU COFFEE PRODUCTION IN TUBU VILLAGE, NORTH CENTRAL TIMOR REGENCY - Kamilaus Konstanse Oki; Emilia K. Kiha; Antonia Maria Clarita Lake (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2026)
This study aims to examine the effect of accessibility on the volume of Tubu coffee production in Tubu Village, North Central Timor Regency. With its supportive geographical characteristics, this village has great potential in developing coffee as a source of livelihood. Through a quantitative approach, this study analyzes the effect of transportation access, electricity access, and social media access on the volume of coffee production. The results show that transportation and electricity access have a significant effect, while social media also makes a positive contribution to product marketing. In this digital era, the use of social media allows coffee farmers to market their products more effectively, reach wider consumers, and increase sales. This study concludes that the development of transportation and electricity infrastructure, as well as the use of social media, are the keys to increasing the volume of Tubu coffee production. Recommendations are given to strengthen this accessibility in order to support village economic development and improve the welfare of the local community.